2016
DOI: 10.1111/ssm.12152
|View full text |Cite
|
Sign up to set email alerts
|

Taking Science Home: Connecting Schools and Families Through Science Activity Packs for Young Children

Abstract: A Framework for K-12 Science Education indicates that introducing young children to scientific and engineering practices, core disciplinary ideas, and crosscutting concepts during the early years is essential for the development of conceptual understanding in science. Unfortunately, science is infrequently included in preschool and primary classrooms, and parents are sometimes uncomfortable engaging their children in science. This article describes the development and initial evaluation of "family science acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…In informal setting scientific knowledge is acquired through internet, social media, television, books and newspapers, for instance (Schäfer et al 2018). In addition to an informal learning environment, home can also act as an encouraging non-formal learning environment for science (Shymansky et al, 2000;Solomon, 2003;Reinhart et al, 2016). Usually, non-formal learning environments are facilitated and hold some often skill-related learning targets, but there are volunteer to participate in, like science clubs, camps, museums, zoos, planetariums, science centers and companies (Eschach, 2007).…”
Section: Home As a Non-formal Learning Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…In informal setting scientific knowledge is acquired through internet, social media, television, books and newspapers, for instance (Schäfer et al 2018). In addition to an informal learning environment, home can also act as an encouraging non-formal learning environment for science (Shymansky et al, 2000;Solomon, 2003;Reinhart et al, 2016). Usually, non-formal learning environments are facilitated and hold some often skill-related learning targets, but there are volunteer to participate in, like science clubs, camps, museums, zoos, planetariums, science centers and companies (Eschach, 2007).…”
Section: Home As a Non-formal Learning Environmentmentioning
confidence: 99%
“…Also, Shymansky et al (2000) reported that as a consequence of hands-on science activities done at home both children and parents found it an enjoyable way to spend time together, while doing something useful. Reinhart et al (2016) researched inquiry-based science activities occurring at home. In their model, families were sent science packages, which contained the inquiry activity and necessary tools.…”
Section: Home As a Non-formal Learning Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Each Family Pack contained interesting science activities aligned with the SEPs in the 3D in the Framework (NRC, 2012) and various early learning standards (e.g., NAEYC, ; ODE, ). The Family Packs were designed to help parents know what to do, have access to background knowledge, and promote high quality discourse (Reinhart et al, ). Each pack included a newsletter with the directions for the investigation, necessary materials for the activity, and a journal sheet for children to record data or visually represent understanding.…”
Section: Description Of the Nurtures Programmentioning
confidence: 99%